Wireless Algorithms, Systems, and Applications 9th International Conference, WASA 2014, Harbin, China, June 23-25, 2014, Proceedings - Cai, Zhipeng; Wang, Chaokun; Cheng, Siyao; Wang, Hongzhi; Gao, Hong (Theoretical Computer Science and General Issues, 2014)
This book constitutes the refereed proceedings of the 9th International Conference on Wireless Algorithms, Systems and Applications, WASA 2014, held in Harbin, China, in June 2014. The 41 revised full papers presented together with 30 invited papers were carefully reviewed and selected from 134 submissions. The papers cover a wide range of topics including cognitive radio networks, wireless sensor networks, cyber-physical systems, distributed and localized algorithm design and analysis, information and coding theory for wireless networks, localization, mobile cloud computing, topology control and coverage, security and privacy, underwater and underground networks, vehicular networks, information processing and data management, programmable service interfaces, energy-efficient algorithms, system and protocol design, operating system and middle-ware support and experimental test-beds and models.